Synthesis, Characterization and Surface Properties of Nano-TiO2 Using a Novel Leaf Extracts - Tariq, Rasha; Edan Al-Mammar, Dunya (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2023)
The main focus of research is on the nature of applications in the fields of science and technology, particularly nanotechnology. In this paper, a simple, non-toxic, inexpensive, and environmentally friendly green method was used to synthesize TiO2 nanoparticles using the extraction of portulacaria afra plant leaves and TiCl4 as a precursor. The synthesized titanium dioxide nanoparticles were characterized by scanning electron microscopy, atomic force microscopy, X-ray diffraction patterns, Fourier transform infrared spectroscopy, and Brunauer-Emmett-Teller analysis. The SEM image of TiO2 nanoparticles showed a few spherical, non-agglomerated particles. The average diameter of the nanoparticles, according to the surface topography of TiO2-NPs, is 70.24 nm. It was found that the average crystalline size was 18.9 nm by utilizing the Debye-Scherrer equation to calculate the size of the crystals. The vibrational mode of Ti-O-Ti exhibits a distinctive peak in the broad band centered at 578.64, 547.78, and 514.99 cm-1, which denotes the development of metal-oxygen bonding, confirming the presence of TiO2-NPs. The specific surface of the synthesized particles was calculated using the Brunauer-Emmett-Teller BET equation.